2020
DOI: 10.1016/s2542-5196(19)30241-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between historical residential redlining and current age-adjusted rates of emergency department visits due to asthma across eight cities in California: an ecological study

Abstract: Background Asthma disproportionately affects communities of colour in the USA, but the underlying factors for this remain poorly understood. In this study, we assess the role of historical redlining as outlined in security maps created by the Home Owners' Loan Corporation (HOLC), the discriminatory practice of categorising neighbourhoods on the basis of perceived mortgage investment risk, on the burden of asthma in these neighbourhoods. MethodsWe did an ecological study of HOLC risk grades and asthma exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 262 publications
(184 citation statements)
references
References 36 publications
8
175
0
1
Order By: Relevance
“…We found similarly reduced odds of preterm birth along with SGA and LBW when comparing births in historically redlined neighborhoods compared to yellow-lined neighborhoods, an effect that was most predominant among Hispanic women and non-Hispanic White women. The association of historical redlining with several other health outcomes have been shown in other studies; our prior work found a 39% increase in asthma emergency department visit rates in redlined California census tracts compared to grade A census tracts [19]. Other studies have identified relationships between historical redlining and current foreclosures on one hand, and self-rated health on the other in Detroit, Michigan as well as tuberculosis cases in Austin, Texas in the 1950s [20,21].…”
Section: Plos Onesupporting
confidence: 64%
See 2 more Smart Citations
“…We found similarly reduced odds of preterm birth along with SGA and LBW when comparing births in historically redlined neighborhoods compared to yellow-lined neighborhoods, an effect that was most predominant among Hispanic women and non-Hispanic White women. The association of historical redlining with several other health outcomes have been shown in other studies; our prior work found a 39% increase in asthma emergency department visit rates in redlined California census tracts compared to grade A census tracts [19]. Other studies have identified relationships between historical redlining and current foreclosures on one hand, and self-rated health on the other in Detroit, Michigan as well as tuberculosis cases in Austin, Texas in the 1950s [20,21].…”
Section: Plos Onesupporting
confidence: 64%
“…For example, a recent analysis by Krieger et al . found an association between historical redlining and risk of preterm birth in New York City, and we previously observed a relationship between redlining and current disparities in rates of asthma-related emergency room visits in California [ 19 , 24 ]. Both studies conceptualize historical redlining as an indicator of government-sanctioned policies that deprived neighborhoods of capital investment and physically segregated people of color in ways that diminished access to services, amenities, and health care resources that are critical to promoting healthy lifestyles and community well-being [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Notably, the 5 neighborhoods highlighted in this study have a high proportion of residents of color and a high prevalence of poverty, in large part due to residential redlining (ie, the systematic denial of federal, local, or private resources by area), resulting in racial segregation that has prevented wealth accumulation among people of color. 51,52 These same neighborhoods have higher rates of preventable hospitalizations, are more susceptible to effects of climate change, 53 and are at higher risk of gentrification. 54 All of these factors have been shown to influence socially mediated health behaviors, such as ACP.…”
Section: Discussionmentioning
confidence: 99%
“…21 Today you can view old redlining maps, which guided where banks were willing to invest, in comparison with rates of asthma, diabetes, and hypertension and see the historical connection between decades of discrimination and chronic illnesses that are primary risk factors for COVID-19 severity. 22 Examples of how institutional discrimination shapes the current distribution of chronic health disparities are too numerous to count, but result from the proximity of nonwhite neighborhoods to factories and other environmental pollutants, 23 poor housing stock that predisposes children specifically to lead and respiratory contaminants, 24 and exposure to discrimination within white institutions that is associated with chronic stress and disease. 25,26 The composition of America's communities, especially in urban areas, remains largely segregated and these patterns also shape where COVID-19 testing locations are present and the accumulation of political power that would allow for shared decision making in responses to the pandemic.…”
Section: Institutional and Systemicmentioning
confidence: 99%